A novel thyristor-based hybrid DC circuit breaker with the ability to identify the type and location of the fault before reclosing the MMC-HVDC grid - Mojtaba Roshani Diz; Behrooz Vahidi; Hasan Rastegar (International Journal of Electrical Power & Energy Systems)
Although HVDC grids offer significant advantages in the widespread integration of renewable sources and the transmission of their generated power to distant areas, distrust remains regarding their performance under fault conditions. So far, multiple DCCBs have been proposed in the literature, which often do not adequately consider the number of semiconductors, reliability, and the requirement for adaptive reclosing capability. This paper introduces a thyristor-based hybrid CB (TB-HCB), incorporating UFD, RCB, thyristors, capacitors, and coupled inductors. In TB-HCB, a thyristor within a diode bridge, along with other commutating components, replaces the LCS, and the disconnection process is performed with coupled inductors and a pre-charged capacitor. The proposed configuration distinguishes permanent and temporary faults using traveling pulse wave theory, thereby minimizing electrical stresses and energy dissipation in the arresters. In this regard, the possibility of fault localization is also provided. Moreover, the impact of varying the parameters of the TB-HCB fault diagnosing section on the injected pulse is also investigated. The simulations have been implemented in the PSCAD/EMTDC to verify the theoretical calculations. Finally, TB-HCB has been compared with some similar existing models.